1998
DOI: 10.1046/j.1365-2923.1998.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Imprecise terms in UK medical multiple‐choice questions: what examiners think they mean

Abstract: Many multiple-choice questions (MCQs) used in medical education in the UK contain undefined, imprecise terms. They are particularly common in true/false items and can be found in classroom tests, published examples of MCQs and, more importantly, in high-stakes examinations which determine a candidate's graduation or membership of a professional body. This study investigated imprecise terms used in some MB BS final examinations and the Part 1 Membership Examination of the Royal College of Physicians. It reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 6 publications
1
24
0
1
Order By: Relevance
“…Other studies revealed that even terms like “never” or “always” which were expected to be rated as absolute “0%” or “100%” both were indicated with a range up to 20% [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies revealed that even terms like “never” or “always” which were expected to be rated as absolute “0%” or “100%” both were indicated with a range up to 20% [10]. …”
Section: Introductionmentioning
confidence: 99%
“…In summary, the existing research indicates that it is a rather difficult task to differentiate between frequency or intensity terms for both medical experts and patients with a depressive disorder or fatigue [8,17,18]. Interindividual congruency and intraindividual stability across time of mental representations of such terms was shown to be rather low.…”
Section: Introductionmentioning
confidence: 94%
“…Wenselijke studentprestaties kunnen dan ook niet goed worden geëvalueerd en op rechtvaardige wijze worden beloond. [6][7] Toetsing binnen de FMW bestaat voor een groot deel uit schriftelijke toetsen met geprecodeerde toetsvragen. De kwaliteit van deze laat echter vaak te wensen over.…”
Section: Inleidingunclassified